ANALISIS SWOT STRATEGI PEMASARAN MELALUI TENAGA LULUSAN PROGRAM STUDI TEKNIK TELEKOMUNIKASI DAN NAVIGASI UDARA (TNU) SEKOLAH TINGGI PENERBANGAN INDONESIA (STPI) SESUAI DENGAN KEBUTUHAN PANGSA PASAR - Pribadi Asih (Politeknik Penerbangan Indonesia Curug, 2017)
Swot Analytical study on STPI Telecommunication and Air Navigation Graduates in accordance with the marketing demand. To archieve organization goals, marketing strategy is required in companies as well as public institutions. This SWOT analyses is applied to meet the marketing demand for the STPI Telecommunication and Air Navigation Graduates. This research is intended to find the correlation between SWOT analyses of STPI Telecommunication and Air Navigation Graduates and their marketing demand. The secondary data is obatained through observation, questionnaire and interview. There are 20 subjects, choosen by using purposive sampling. The data is analyzed by using pearson correlation followed by t-test consulted to t-table. The result shows that the r is 0.897. Thus, it is summarized that the SWOT analyses is positively correlated to the marketing demand.